Analysis of Facilities and Infrastructure Needs to Support Learning in Inclusive Schools: A Case Study of SDN Sawocangkring - Haris Ainul Muiz; Bachtiar Hariyadi (Responsive: Jurnal Manajemen Pendidikan Islam, 2026)
This study discusses the analysis of facilities and infrastructure needs to support inclusive learning at SDN Sawocangkring. Facilities and infrastructure are essential components in creating a learning environment that is accessible, equitable, and supportive of the development of all students, including Children with Special Needs (ABK). The purpose of this research is to examine the existing condition of facilities and infrastructure, identify unmet needs, and explore the supporting and inhibiting factors in providing inclusive educational facilities. This research employed a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that: (1) some basic facilities such as ramps, disability-friendly toilets, and specialized learning aids are not yet available; (2) urgent needs include physical accessibility, specific learning media, and therapy rooms; (3) supporting factors involve the commitment of teachers, parents, and external stakeholders, while inhibiting factors mainly consist of financial constraints and the absence of comprehensive policies regulating inclusive infrastructure provision. Overall, there is a significant gap between actual conditions and ideal standards, which calls for collaborative and sustainable strategies to enhance the quality of inclusive education at SDN Sawocangkring.